Effect of fruit size and processing time on vacuum impregnation parameters of cantaloupe and apple - Phianmongkhol A. (Chiang Mai University, 2015)
This study evaluated the effect of two fruit sizes (3.5×2.5×1.0 and 1.2×1.2×0.8 cm3) and processing time (impregnation and relaxation times; both for 10 and 20 min), on some vacuum impregnation parameters of cantaloupe and apple. Fruit size and processing time significantly affected the mass fraction of fruit occupied by impregnation liquid (X value) and the effective porosity (εe) of apples more than cantaloupe. High surface area of fruit and long processing times allowed for significant liquid penetration into the fruit. This study has shown that the effectiveness of vacuum impregnation is a surface-controlled phenomenon.